SIMULASI BANTUAN HIDUP DASAR DENGAN MOTION GRAPHIC TERHADAP TINGKAT PENGETAHUAN KARANG TARUNA DALAM MENOLONG KORBAN KECELAKAAN LALU LINTAS - Ardiansyah, Ganda; Utami, Rahayu Budi; Permatasari, Indah (JURNAL SABHANGA, 2023)
Introduction: Youth knowledge about basic life support plays an important role in increasing traffic accident victims to survive. However, in fact, it was found that the youth youth organizations did not know both theoretically and practically about basic life support. The purpose of this study was to determine the effect of basic life support simulation with motion graphics on the level of knowledge of youth organizations in helping traffic accident victims in Manyung Rejo Hamlet, Bagor Kulon Village, Bagor District, Nganjuk Regency.